ID-based multi-receiver signcryption scheme in the standard model. (2017) - Yu, Zhimin; Jing, Zhengjun; Yang, Hua; Gu, Chunsheng
Currently, the network multicast in network and internet services are widely used, and how to ensure secure data transmission and non-repudiation has been a hot issue. In order to ensure data confidentiality and non-repudiation in multicast that has lower cost of data transmission and computing, we propose an ID-based multi-receiver signcryption scheme in the standard model based on multilinear maps. In our construction, the number of recipients is unlimited and each receiver decrypts ciphertext using his private key and verifies the identity of the sender. At the same time, the identity-based design has important advantages in that it eliminates the large overhead of having to store and verify a set of verification keys. Based on the hardness assumption of the graded Diffie-Hellman problem, we prove that the proposed scheme can achieve the message confidentiality under selective multi-ID, chosen message attack and the signcryption is unforgeable under selective ID, chosen message attack.